Synthesis of (±)-7-Hydroxylycopodine - Lin, Hong-Yu (2011)
[Image: see text] A 6 step synthesis of (±)-7-hydroxylycopodine has been achieved in 5% overall yield. In the key step, a Prins cyclization of a bicyclic keto alkyne in 60% H(2)SO(4) forms a tricyclic dihydroxy amino ketone.